2009
DOI: 10.1371/journal.pone.0004930
|View full text |Cite
|
Sign up to set email alerts
|

I Feel what You Feel if You Are Similar to Me

Abstract: Social interactions are influenced by the perception of others as similar or dissimilar to the self. Such judgements could depend on physical and semantic characteristics, such as membership in an ethnic or political group. In the present study we tested whether social representations of the self and of others could affect the perception of touch. To this aim, we assessed tactile perception on the face when subjects observed a face being touched by fingers. In different conditions we manipulated the identity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
88
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 32 publications
(41 reference statements)
14
88
1
1
Order By: Relevance
“…Contrary to our expectations, the role of perspective was not dependent on the type of visual information, suggesting that any hand observed in first-person perspective facilitated detection, as compared with third-person perspective. This effect of perspective taking on detection accuracy is in line with research done by Serino et al (2009). These researchers showed that vision facilitated tactile perception mostly when self-other similarity was high (e.g., by manipulating the visual appearance and political opinions between an observer and the observed person).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Contrary to our expectations, the role of perspective was not dependent on the type of visual information, suggesting that any hand observed in first-person perspective facilitated detection, as compared with third-person perspective. This effect of perspective taking on detection accuracy is in line with research done by Serino et al (2009). These researchers showed that vision facilitated tactile perception mostly when self-other similarity was high (e.g., by manipulating the visual appearance and political opinions between an observer and the observed person).…”
Section: Discussionsupporting
confidence: 87%
“…No study has investigated this idea. However, studies have indicated that the adoption of a first-person perspective, by means of either an experimental paradigm or instructions or visual appearance facilitates/affects the detection of somatosensory stimuli (Loggia, Mogil, & Bushnell, 2008;Serino, Giovagnoli, & Làdavas, 2009;Serino et al, 2008). In the study of Loggia et al, similarity was manipulated by showing participants video interviews with an actor in which empathy for the actor was manipulated.…”
mentioning
confidence: 99%
“…Second, manipulation of unisensory signals rarely induces alteration in body perception (but see Longo, Kammers, Gomi, Tsakiris, & Haggard, 2009). Rather, as the cases of multisensory illusions reviewed here suggest, experience of the body might result from multisensory integration mechanisms (see Blanke, 2012;Serino & Haggard, 2010).…”
Section: Unisensory Body Representationsmentioning
confidence: 91%
“…Thus, a full understanding of human cognition ought to take into account how cognition shapes and is shaped by social interaction. The body is our interface with others (see e.g., Adolphs, 2009;Decety & Lamm, 2007;Gallese, Keysers, & Rizzolatti, 2004;Saxe, 2006), and therefore it is possible that social interactions shape the experience we have of our body (Ambrosini, Blomberg, Mandrigin, & Costantini, 2013;Cardellicchio, Sinigaglia, & Costantini, 2012;Cardini, Tajadura-Jimenez, Serino, & Tsakiris, 2012;Costantini, Ambrosini, Sinigaglia, & Gallese, 2011;Costantini, Committeri, & Sinigaglia, 2011;Costantini et al, 2013;Serino, Giovagnoli, & Ladavas, 2009;Teneggi, Canzoneri, di Pellegrino, & Serino, 2013).…”
Section: Limits Of the Modelmentioning
confidence: 99%
“…1 One account posits that impaired self-other representations could contribute to a disinhibition of normal somatosensory mirroring mechanisms in individuals with MTS Fitzgibbon et al 2012;Ward & Banissy, In Press). This account builds on findings in non-synaesthetic individuals (Serino, Giovagnoli, & Làdavas, 2009) which show that observing another person being touched enhances the perception of touch on the self, but only when the other is perceived as being similar to the self (and is therefore not a clear 'other').…”
Section: Introductionmentioning
confidence: 64%